2014
DOI: 10.3390/md12052840
|View full text |Cite
|
Sign up to set email alerts
|

Three New Resveratrol Derivatives from the Mangrove Endophytic Fungus Alternaria sp.

Abstract: Three new resveratrol derivatives, namely, resveratrodehydes A–C (1–3), were isolated from the mangrove endophytic fungus Alternaria sp. R6. The structures of these compounds were elucidated by analysis of their MS, 1D and 2D NMR spectroscopic data. All compounds showed broad-spectrum inhibitory activities against three human cancer cell lines including human breast MDA-MB-435, human liver HepG2, and human colon HCT-116 by MTT assay (IC50 < 50 μM). Among them, compounds 1 and 2 both exhibited marked cytotoxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…from Vitis vinifera, Shi et al 2012; Alternaria sp. from a mangrove plant Myoporum bontioides; Wang et al 2014b), emtomopathogenic bacteria (Photorhabdus luminescens, Eleftherianos et al 2007; Bacillus sp., Kumar et al 2012), several edible mushrooms (Peng et al 2015), sponge (Antarctic sponge Kirkpatrickia variolosa, Jayatilake and Baker 1995), and moth larva (dried silkworm larva of Bombyx mori, Kikuchi et al 2004). A recent transcriptome analysis provided the evidence at the gene level that stilbenes in the endophytic fungus Alternaria could be synthesized by CHS (Che et al 2016), and a recent structural analysis revealed that the stilbene 2-isoprpyl-5-[(E)-2-phenylvinyl] benzene-1,3-diol in bacteria Photorhabdus is synthesized by the collaboration of two enzymes, the unusual b-ketosynthase StlD and the aromatase StlC (Mori et al 2016).…”
Section: Stilbene Distribution Contents and Localizationmentioning
confidence: 99%
“…from Vitis vinifera, Shi et al 2012; Alternaria sp. from a mangrove plant Myoporum bontioides; Wang et al 2014b), emtomopathogenic bacteria (Photorhabdus luminescens, Eleftherianos et al 2007; Bacillus sp., Kumar et al 2012), several edible mushrooms (Peng et al 2015), sponge (Antarctic sponge Kirkpatrickia variolosa, Jayatilake and Baker 1995), and moth larva (dried silkworm larva of Bombyx mori, Kikuchi et al 2004). A recent transcriptome analysis provided the evidence at the gene level that stilbenes in the endophytic fungus Alternaria could be synthesized by CHS (Che et al 2016), and a recent structural analysis revealed that the stilbene 2-isoprpyl-5-[(E)-2-phenylvinyl] benzene-1,3-diol in bacteria Photorhabdus is synthesized by the collaboration of two enzymes, the unusual b-ketosynthase StlD and the aromatase StlC (Mori et al 2016).…”
Section: Stilbene Distribution Contents and Localizationmentioning
confidence: 99%
“…Compounds 1 – 9 were examined for their cytotoxic activities against three human tumor cell lines, including a human breast cancer cell line (MDA-MB-435), a human gastric cancer cell line (SGC-7901), and a human lung adenocarcinoma epithelial cell line (A549) by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2 H -tetrazolium bromide) assay, as described in the liturature [24] using epirubicin as positive control. The results are presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Gray, known as a semi-mangrove medicinal plant, is a small evergreen shrub distributed along the coastal regions of several Asian counties [23]. As part of our ongoing search for biologically active and/or structurally novel metabolites of the endophytic fungi from Myoporum bontioides [24,25], the fungus Penicillium chrysogenum (collection No. V11) harbored inside the normal vein attracted our interests due to its antifungal activity exhibited by the methanol extract in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, resveratrodehyde C, isolated from the mangrove‐derived endophytic fungus Alternaria sp. R6, exhibited an IC 50 of 41.86 μM in HepG2 cell line (Wang et al, ). Both of these fungal metabolites showed a degree of cytotoxic activity similar to that observed for the compounds from N. siamensis KUFA 0017 against this hepatocellular carcinoma cell line.…”
Section: Discussionmentioning
confidence: 99%